OPPORTUNITIES FOR FURTHER EXPANSION OF THE HABEAS CORPUS INSTITUTION IN THE REPUBLIC OF UZBEKISTAN (ON THE EXAMPLE OF INVESTIGATING JUDGES):AN ANALYSIS OF NATIONAL LEGISLATION - Matmurotov Alibek Ravilovich (Modern American Journals, 2026)
This scholarly article provides a comprehensive analysis of the theoretical and legal essence of the habeas corpus institution, its content, as well as its role and significance as reflected in and applied within the legislation of the Republic of Uzbekistan. In addition, the article examines the legal nature of the concept of the investigating judge and its powers through a comparative legal analysis based on national legislation and the practice of foreign states. In the course of the research, the importance of this institution in ensuring the reliable protection of citizens’ constitutional rights and freedoms, as well as legally protected interests, is substantiated, and the necessity of its further improvement within the national judicial and legal system is scientifically justified.
Keywords: Habeas corpus institution, investigating judge, pre-trial proceedings, judicial supervision, constitutional rights and freedoms, personal liberty and inviolability, fair trial, criminal procedural guarantees.